Heiligenhafen and the Wetland Convention - Matthews, G V T (Wildfowl, 1975)
Report on the fifth in a series of International Conferences on the Conservation of Wetlands and Waterfowl held 2nd-6th December 1974 at Heiligenhafen, on the Baltic coast.